PENYUSUNAN DATA JAJANAN KHAS PRODUKSI INDUSTRI MIKRO DI DESA GUNTURMADU DENGAN TENIK WAWANCARA TERSTRUKTUR - Slamet, Slamet; Triwibowo, Deny Nugroho (ABDI MAKARTI, 2024)
Gunturmadu Village is a village in Mojotengah District, Wonosobo Regency, Central Java. The potential of agricultural commodities in Gunturmadu Village has not been utilized optimally because most of the agricultural products are sold directly without being processed first. There are only a few home industries on a micro scale that process agricultural products into typical snacks whose management from production to marketing is still carried out traditionally. This community service program will focus on typical dry snacks which have the potential to be developed, especially for packaging and online marketing. The author carried out a community service program by compiling data on typical snacks produced by the micro industry in Gunturmadu Village using structured interview techniques. The interview data was then processed and edited into a catalog book of typical snacks from Gunturmadu Village, resulting in 20 typical dry snacks. It is hoped that the catalog book for typical dry snacks produced by micro industries in Gunturmadu Village in 2023 will become literature and can ignite the enthusiasm of micro industry players and the younger generation to develop micro industries in Gunturmadu Village.